RCA Analysis With Selected Product: Modified Approach Applied to Indonesian Export - Jongkers Tampubolon (Universitas Negeri Malang, 2019)
Recognition of the competitiveness of various export commodities is very important to design industrial policies which is then shaping the country 's structural transformation, such as to reallocate labors to activities outside of sector with lower comparative advantage. The most popular comparative advantage measurement approach is Revealed Comparative Advantage (RCA) introduced by Balassa in 1965. Eventhough Balassa's RCA very popular, it has received a lot of criticism and improvement effort especially related to its asymmetric distribution and consistency (ranking bias). This present study introduced a new method to increase the predictive power of Balassa's RCA while maintaining the simplicity principle of calculation and convenience in dealing with data availability by selecting product included in the analysis. The study revealed that by selecting the product limited to the top 250 export (from 1,259 products in HS 4-digit), it is able to correct (restore) the position of Indonesian manufacturing sector as a competitive sector (RCA> 1) reflected by the position of the sector as top 10 export, based on export share (export value). This approach also provided a new understanding of Indonesia's export competitiveness in the Chinese market, especially after the implementation of the ASEAN-China FTA in 2010.